Diversity of phenotypically non-dermatophyte, non-Aspergillus filamentous fungi causing nail infections: importance of accurate identification and antifungal susceptibility testing - Chi-Ching Tsang; James Y. M. Tang; Ka-Fai Chan; Chun-Yi Lee; Jasper F. W. Chan; Antonio H. Y. Ngan; Mei Cheung; Eunice C. L. Lau; Xin Li; Ricky H. Y. Ng; Christopher K. C. Lai; Kitty S. C. Fung; et al. (Emerging Microbes and Infections, 2019)
ABSTRACTOnychomycosis is most commonly caused by dermatophytes. In this study, we examined the spectrum of phenotypically non-dermatophyte and non-Aspergillus fungal isolates recovered over a 10-year period from nails of patients with onychomycosis in Hong Kong. A total of 24 non-duplicated isolates recovered from 24 patients were included. The median age of the patients was 51 years, and two-thirds of them were males. One-third and two-thirds had finger and toe nail infections respectively. Among these 24 nail isolates, 17 were confidently identified as 13 different known fungal species, using a polyphasic approach. These 13 species belonged to 11 genera and ≥9 families. For the remaining seven isolates, multilocus sequencing did not reveal their definite species identities. These seven potentially novel species belonged to four different known and three potentially novel genera of seven families. 33.3%, 41.7% and 95.8% of the 24 fungal isolates possessed minimum inhibitory concentrations of >1 µg/mL to terbinafine, itraconazole and fluconazole, respectively, the first line treatment of onychomycosis. A high diversity of moulds was associated with onychomycosis. A significant proportion of the isolates were potentially novel fungal species. To guide proper treatment, molecular identification and antifungal susceptibility testing should be performed for these uncommonly isolated fungal species.